2015
DOI: 10.5468/ogs.2015.58.5.359
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hypoalbuminemia is a risk factor for 30-day morbidity after gynecological malignancy surgery

Abstract: ObjectiveTo determine the relationship between preoperative hypoalbuminemia and the development of complications after gynecological cancer surgery, as well as postoperative bowel function and hospital stay. MethodsThe medical records of 533 patients with gynecological cancer surgery at Konkuk University Hospital between 2005 and 2013 were reviewed. Serum albumin level <3.5 g/dL was defined as hypoalbuminemia. All perioperative complications within 30-days after surgery, time to resumption of normal diet and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
(48 reference statements)
2
21
0
2
Order By: Relevance
“…The mortality rate in the present study is comparable to other studies which were associated hypoalbuminemia. 26 The incidence of complication following gastric surgery was the highest in our study similar to that observed from Spain in 2009 in a retrospective review of 158 patients undergoing elective gastrointestinal study. 21 A multicenter study of 54,215 patients following major noncardiac surgery in 1999 highlighted that a decrease in serum albumin from concentrations greater than 46 g/L to less than 21 g/L was associated with an exponential increase in mortality rates from less than 1% to 29% and in morbidity rates from 10% to 65% following non-cardiac surgery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mortality rate in the present study is comparable to other studies which were associated hypoalbuminemia. 26 The incidence of complication following gastric surgery was the highest in our study similar to that observed from Spain in 2009 in a retrospective review of 158 patients undergoing elective gastrointestinal study. 21 A multicenter study of 54,215 patients following major noncardiac surgery in 1999 highlighted that a decrease in serum albumin from concentrations greater than 46 g/L to less than 21 g/L was associated with an exponential increase in mortality rates from less than 1% to 29% and in morbidity rates from 10% to 65% following non-cardiac surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Our hypoalbuminemic patients had a significantly higher rate of postoperative complications (26.4% vs 5.6%, P=0.004) consistent with that reported in the literature. [21][22][23][24][25][26] Hypoalbuminemic patients have higher risk of having postoperative complications (37.5% vs. 21.3%, P = 0.014) following rectal cancer surgery which is similar to that observed in our study. 11 In the present study , a multivariate analysis of the relationship of serum albumin and complications showed that a preoperative hypoalbuminemia increased the risk of complications by 5.2 fold which is comparable to 5.6 fold observed in the series of 524 patients undergoing gastrointestinal surgery in Ireland in 2010.…”
Section: Discussionsupporting
confidence: 86%
“…These variables are all included in the ACS NSQIP Surgical Risk Calculator. Low serum albumin has been shown to be associated with poor surgical outcomes [11-13]. A cut off of albumin < 3.4 was used as this considered abnormal in our hospital laboratory and was thus used in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An albumin level provides a good assessment of the patient's nutritional status: improving preoperative hypoalbuminemia is an independent predictor for preventing severe postoperative complications and a prognostic parameter for overall survival in surgical cancer patients . Iron‐deficiency anemia also is associated with postoperative morbidity and mortality and should be corrected before elective surgery to avoid adverse effects, the need for a blood transfusion, or both .…”
Section: Preoperative Patient Care and Preparationmentioning
confidence: 99%